Extracellular vesicle miR-425-5p promotes visceral fat reduction via DACT1 suppression in SGLT2i-treated diabetes - Park, Jae-Hyung; Nguyen, Thi Nhi; Shim, Hye Min; Bae, Yun-Ui; Yu, Gyeong Im; Kang, Junho; Ha, Eun Yeong; Cho, Hochan (Frontiers in Endocrinology, 2025)
ObjectiveIn type 2 diabetes (T2D), plasma-derived extracellular vesicle (EV)-microRNAs (miRNAs) contribute to insulin resistance and β-cell dysfunction. Sodium-glucose cotransporter 2 inhibitors (SGLT2i) lower blood glucose by promoting urinary glucose excretion and are associated with weight loss, although the underlying mechanisms remain unclear.MethodsThis study was conducted in two phases. In the screening phase, plasma-derived EV miRNA profiles were analyzed by small RNA sequencing in 13 patients with newly diagnosed, treatment-naive T2D at baseline and after 12 months of SGLT2i therapy. In the validation phase, expression of selected miRNAs was quantified by real-time PCR in an independent cohort of 30 patients at baseline and after 6 and 12 months of treatment. The functional roles of candidate miRNAs were examined in 3T3-L1 adipocytes.ResultsSmall RNA sequencing identified 18 plasma-derived EV miRNAs exhibiting >1.5-fold expression changes after 12 months of SGLT2i therapy. Quantitative PCR confirmed that five EV miRNAs were significantly upregulated post-treatment. Among these, miR-425-5p showed a strong inverse correlation with waist circumference and visceral fat area. Functional assays in 3T3-L1 adipocytes demonstrated that miR-425-5p suppressed adipogenic differentiation and lipid accumulation by downregulating DACT1, one of its predicted target genes, and reducing DACT1-reporter activity.ConclusionPlasma-derived EV miR-425-5p, increased by long-term SGLT2i therapy in T2D patients, may inhibit adipocyte differentiation and lipogenesis via DACT1 suppression. These findings suggest a possible mechanistic link through which SGLT2i treatment may ameliorate visceral obesity.